A BL-CC Converter-Based BLDC Motor Drive for Marine Electric Vehicle Applications. (1st June 2022) - Shukla, Tanmay; Kalla, Ujjwal Kumar
Abstract : This article presents a BLDC (permanent magnet brushless DC) motor drive for marine electric vehicle (MEV) application. The presented scheme uses bridgeless canonical cell (BL-CC) converter with center-tapped inductor (shown as two separate inductors for analysis purpose) for source-side power factor correction (PFC); however, the BL-CC converter requires two inductors. In the presented scheme use of one center-tapped inductor eliminates the requirement of one extra inductor. Thus, center-tapped inductor usage in BLDC motor drive results in decrement in components count. The BL-CC converter-based BLDC motor drive scheme do not require extra back-feeding diodes like other bridgeless (BL) schemes, but it uses inbuilt antiparallel diodes of insulated gate bipolar transistor (IGBT) switches for the same purpose this again leads to decrement in required component count. In this work, PFC BL-CC converter is operated in discontinuous inductor current (DIC) mode to attain better power quality. The DIC mode operation requires only one voltage sensor to sense DC-link voltage, whereas in continuous conduction mode (CCM), the sensor requirement increases to three (two voltage sensors and one current sensor). The PFC BL-CC converter also eliminates the diode bridge rectifier stage. The elimination of one extra inductor, two extra back-feeding diodes, DBR stage and also requirement of only one voltage sensor in DIC mode operation instead of three sensors for CCM implies reduction in components count which implies the reduction in cost and also the volume and weight of the BLDC motor drive. The weight reduction for marine (on-board) electric vehicle is very important as this enhances the vehicle performance. This paper also presents the detailed mathematical modeling and stability analysis of presented BL-CC converter using pole zero map and Bode plot. The BL-CC converter-based BLDC motor driving system for MEV application for DIC mode operation has been developed in the laboratory as well as on MATLAB/Simulink platform and simulated MATLAB and real-time experimental results have been presented to validate the presented BLDC motor drive under steady-state and dynamic operating conditions.